Australian public's awareness of stroke warning signs improves after national multimedia campaigns - Bray, Janet; Johnson, R.; Trobbiani, K.; Mosley, I.; Lalor, E.; Cadilhac, D. (2013)
Background and Purpose: The aim of this study was to examine the reach and impact of the National Stroke Foundation (NSF) multimedia stroke warning sign campaigns across Australia. Methods: A total of 12 439 surveys were performed across 6 states during 6 years on random state–weighted samples of Australians ≥40 years old. Results: Awareness of stroke advertising increased 31% to 50% between 2004 and 2010 (P<0.001), as did the unprompted recall of ≥2 most common stroke warning signs 20% to 53% (P<0.001). Awareness of stroke advertising was independently associated with recalling ≥2 common signs (adjusted odds ratio=1.88, 95% confidence interval [1.74–2.04]; P<0.001). Awareness was not greater in respondents with previous stroke or risk factors, except atrial fibrillation. Conclusions: The Australian public’s awareness of stroke warning signs has improved since commencement of the NSF campaigns commensurate with greater awareness of stroke advertising. Public education efforts are worthwhile, and future efforts should focus on groups identified with low awareness or those at high risk of stroke.